"Cladonia verticillata" ("Cladoniaceae", Ascomycota), new record to Iberian Peninsula - Pino-Bodas, Raquel; P. Martín, María; Stenroos, Soili; Burgaz, Ana Rosa (Botanica Complutensis, 2013)
The identity of a putative collection of Cladonia verticillata is assessed by means of ITS rDNA region. The phylogenetic analyses confirmedthat this specimen belongs to C. verticillata, and this species is reported as new to Iberian Peninsula.